Influence of Local Distant Inducing Cryoeffect and Time Factor on Humoral Immunity of Patients with Hypothyrosis, Operated for Autoimmune Thyroiditis - Mikityuk, M. R.; Karachentsev, Yu. I. (Problems of Cryobiology and Cryomedicine, 2004)
The influence of local distant inducing cryoeffect (LDIC) and time factor on the immunity humoral link indices in 25 patients with hypothyrosis, operated for autoimmune thyroiditis (AIT), was studied in dynamics. LDIC was shown to cause the positive changes in the system of humoral anti-thyroid immunity for the term more than 6 months. A gradual fading of immune-modulating effect 9 months later stipulates the necessity for a repeated LDIC application.